2021
DOI: 10.3389/fcell.2021.633704
|View full text |Cite
|
Sign up to set email alerts
|

Human Atrial Fibrillation Is Not Associated With Remodeling of Ryanodine Receptor Clusters

Abstract: The release of Ca2+ by ryanodine receptor (RyR2) channels is critical for cardiac function. However, abnormal RyR2 activity has been linked to the development of arrhythmias, including increased spontaneous Ca2+ release in human atrial fibrillation (AF). Clustering properties of RyR2 have been suggested to alter the activity of the channel, with remodeling of RyR2 clusters identified in pre-clinical models of AF and heart failure. Whether such remodeling occurs in human cardiac disease remains unclear. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Yin et al found a reduced association between junctophilin-2 and RyR2 in RyR2-R420Q +/− knock-in mice measured by co-immunoprecipitation, suggesting this could contribute to the redistribution of cluster size that results from this mutation [ 77 ]. In contrast to work in the experimental sheep heart failure [ 89 ], Munro et al found RyR2 cluster and CRU properties to be unaltered in atrial myocytes from human patients with persistent AF versus patients without AF [ 90 ]. Here, the non-AF samples came from patients requiring coronary artery bypass graft surgery and may have experienced some degree of prior cardiac remodeling, which could contribute to the lack of CRU disruption observed.…”
Section: Ryr2 Subcellular Geometry Influences Cardiac Ca 2+...mentioning
confidence: 91%
See 1 more Smart Citation
“…Yin et al found a reduced association between junctophilin-2 and RyR2 in RyR2-R420Q +/− knock-in mice measured by co-immunoprecipitation, suggesting this could contribute to the redistribution of cluster size that results from this mutation [ 77 ]. In contrast to work in the experimental sheep heart failure [ 89 ], Munro et al found RyR2 cluster and CRU properties to be unaltered in atrial myocytes from human patients with persistent AF versus patients without AF [ 90 ]. Here, the non-AF samples came from patients requiring coronary artery bypass graft surgery and may have experienced some degree of prior cardiac remodeling, which could contribute to the lack of CRU disruption observed.…”
Section: Ryr2 Subcellular Geometry Influences Cardiac Ca 2+...mentioning
confidence: 91%
“…Recent advances in super-resolution optical microscopy have further enabled the detection and characterization of RYR2 organization at near single molecule level in both 2D [ 86 , 87 ] and 3D [ 88 ], which was previously not possible due to diffraction limitations of conventional confocal microscopes. These recent investigations in rodent, sheep, and human myocytes have shown that RyR2 clusters typically consist of ~15–20 channels that can be sparsely packed [ 86 , 88 , 89 , 90 ]. This is much smaller than previous estimates of ~100 RyR2 per cluster, calculated from thin sectioning that relied on assumptions of complete filling and circular geometry [ 91 ].…”
Section: Ryr2 Subcellular Geometry Influences Cardiac Ca 2+...mentioning
confidence: 99%
“…AFib CRUs were more fragmented and contained more RyRs, dispersed over a larger area than healthy cell controls ( MacQuaide et al, 2015 ). However, in a recent study of RyR2 clustering in diseased atrial myocytes from human AFib patients, no dispersion or reorganization of RyR2 was observed suggesting that RyR2 reorganization is not a necessary component of the Ca 2+ leak and arrhythmogenicity associated with human AFib ( Munro et al, 2021 ).…”
Section: Dyadic Calcium Channel Displacement and Mis-regulation During Cardiac Pathologymentioning
confidence: 99%
“…The rat and sheep studies discussed above suggest that altered nanoscale organization of RyR2 in cardiomyopathies can contribute to the altered kinetics of Ca 2+ release and the disease phenotype in these species. Further investigations are needed to determine whether the same can be said for multi-factorial human cardiomyopathies given that human AFib does not appear to exhibit this phenomenon ( Munro et al, 2021 ).…”
Section: Dyadic Calcium Channel Displacement and Mis-regulation During Cardiac Pathologymentioning
confidence: 99%
“…In heart failure (HF), increased non-spark leak, increased spark size, and decreased spark frequency were observed ( Kolstad et al, 2018 ); in atrial fibrillation (AF), increased duration, frequency, and time to peak of sparks were observed ( Macquaide et al, 2015 ). The changes observed at the cellular level might stem not only from changes in RyR gating but also from a changed structure of the calcium release sites that occurred in some ( Macquaide et al, 2015 ; Kolstad et al, 2018 ) but not all models of cardiac disease ( Munro et al, 2021 ). It is not known whether the changes observed in diseased cardiac myocytes are due to changes in the action of Mg 2+ , but the RyR inhibitor dantrolene, which requires Mg 2+ to exert its effect ( Choi et al, 2017 ), was shown to have beneficial effects in AF ( Hartmann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%